Sesquiterpene Lactones Modulated DNA Methylation through Inhibition of DNMTs in Ovarian Cancer Cells - Idowu Fadayomi; Suat Sari; Mark Kitchen; Jóhannes Reynisson; Nicholas Forsyth; Wen-Wu Li (Elsevier, 2022)
Inappropriate DNA methylation of tumour suppressor genes can affect their expression and function, and as such, DNA methylation has been a promising target for anti-cancer therapy. In gynaecological malignancy, ovarian cancer has the highest associated rate of mortality. This study investigated the in vitro cytotoxicity of four sesquiterpene lactones (SLs), including dehydroleucodine (Deh), alantolactone (Ala), costunolide (Cos), and parthenolide (Pat), and their effect on DNA methylation in ovarian cancer. The binding of the SLs with DNA methyltransferases (DNMTs) were studied using molecular docking. The in vitro antiproliferative activity was evaluated in human ovarian cancer cell lines. SL-induced pro-apoptotic activity and effect on cell cycles was evaluated using enzymatic assays and flow cytometry. Global DNA methylation and DNMTs activity by SLs were measured using ELISA assays. DNA methylation and expression of tumour suppressor genes MHL1 and PTEN were quantified using pyrosequencing and RT-qPCR, respectively. SLs displayed strong binding to DNMT1, 3A and 3B in silico, with Deh exhibiting the strongest binding. SLs showed cytotoxicity in the order of Deh ≈ Ala > Pat > Cos, induced apoptosis, and arrested cell cycle at G2/M phase. Deh and Ala possessed DNMT inhibitory activity, reduced global and gene-specific DNA methylation, and increased expression of notable MHL1 and PTEN, which could contribute to the induction of apoptosis and cell death. In conclusion, Deh and Ala, possess strong cytotoxicity and hold the exciting potential as novel therapeutic agents in ovarian cancer.